"عالمی امن میں اسلام کا کردار The Role of Islam in establishing World-wide Peace " - بشىر احمد رند; شازىہ رمضان (الإيضاح, 2015)
We live in a global village. The cyber world has brought together people and shurnk the distences, yet multi cultural, multi ethinic and multi national has become the norm of the day. There is virtually no such place, no town, no village, city or state where people from diverse backgrounds speaking diffirent lagnuages and professing diffirent creeds live. This diveristy and variety is the essence of life. This paper analyzes various ways of establishing peace in the light of Islamic teachings. It finds out the causes of quarrels and disputes in different nations so that they may be prevented to make the world peaceful.